Annual Research Review: Resilience – clinical implications. (28th September 2012) - Rutter, Michael
<x xml:space="preserve">Abstract</x> Background: It is a universal finding that there is huge heterogeneity in people's responses to all kinds of stress and adversity. Resilience is an interactive phenomenon that is inferred from findings indicating that some individuals have a relatively good outcome despite having experienced serious adversities. Methods: Resilience can only be inferred if there has been testing of environmental mediation of risks and quantification of the degree of risk. The use of 'natural experiments' to test environmental mediation is briefly discussed. The literature is then reviewed on features associated with resilience in terms of (a) those that are neutral or risky in the absence of the risk experience (such as adoption); (b) brief exposure to risks and inoculation effects; (c) mental features (such as planning, self‐regulation or a sense of personal agency); (d) features that foster those mental features; (e) turning point effects; (f) gene‐environment interactions; (g) social relationships and promotive effects; and (h) the biology of resilience. Results: Clinical implications are considered with respect to (a) conceptual implications; (b) prevention; and (c) treatment. Conclusion: Resilience findings do not translate into a clear programme of prevention and treatment, but they do provide numerous leads that focus on the dynamic view of what may be involved in overcoming seriously adverse experiences.